2009
DOI: 10.1007/s10669-009-9244-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes towards gas flaring in the Niger Delta, Nigeria

Abstract: Gas flaring is the burning of crude oil's associated gas. In Nigeria's Niger Delta, the flaring process is usually very close to communities and their farmlands and has been implicated in serious environmental degradation of the region. Studies have suggested links between gas flaring and health problems in the communities and others have established relationships between gas flaring and poor agricultural yields. This study explores how the people in the region perceive gas flaring and what their attitudes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…Duru stated that one of the main types and causes of environmental degradation in the Niger Delta is the result of gas flaring and that most of the gas flaring that occurs in the Niger Delta region is around oil wells that are close to farmlands and dwelling homes [20]. Edino et al noted that the 56.6 million metric tons of associated gas flared daily in Nigeria are equivalent to about 16% of the total gas flared in the world and that the environmental damage is yet to be fully estimated, but anecdotal evidence suggests it is equally colossal [21]. Consequently, the oil firms in Nigeria account for more greenhouse gas emissions than all other sources in sub-Saharan Africa combined [32].…”
Section: The Concept Of Environmental Degradationmentioning
confidence: 99%
“…Duru stated that one of the main types and causes of environmental degradation in the Niger Delta is the result of gas flaring and that most of the gas flaring that occurs in the Niger Delta region is around oil wells that are close to farmlands and dwelling homes [20]. Edino et al noted that the 56.6 million metric tons of associated gas flared daily in Nigeria are equivalent to about 16% of the total gas flared in the world and that the environmental damage is yet to be fully estimated, but anecdotal evidence suggests it is equally colossal [21]. Consequently, the oil firms in Nigeria account for more greenhouse gas emissions than all other sources in sub-Saharan Africa combined [32].…”
Section: The Concept Of Environmental Degradationmentioning
confidence: 99%
“…Results from the analysis revealed that the total cost of gas flared from 1972 to 1998 was 4,493,348.23 billion USD out of 6,160,462.29 billion USD cost for gas production. Gas flaring in Nigeria's oil and gas industry is an ongoing occurrence resulting in significance loss of the nation's resources for every amount of gas produced yearly [3, 6,14,15]. Figure 4 shows the annual trend in cost of gas produced and gas flared from 1972 to 1998.…”
Section: Cost Of Gas Produced and Gas Flared In Nigeria's Oil And Gasmentioning
confidence: 99%
“…The natural gas reserves in Nigeria have prospects to reduce energy-related costs through increased efficiency [4] but gas flaring has been a major cause of environmental pollution contributing significantly to GHG emissions, a waste of a significant energy source and loss of revenue to the country [6,14,15]. From a global perspective gas flaring in the petroleum and natural gas sector constitutes a significant environmental problem and a waste valuable energy source [16].…”
Section: Introductionmentioning
confidence: 99%
“…Emissions from industrial flares contribute to global warming. The implications of global warming have been linked to the melting of ice and the rising of sea level, which can lead to flooding and tsunamis across the globe (Anomohanran, 2012;Azam and Farooq, 2005;Edino et al, 2010;Hassan and Kouhy, 2013;Joseph et al, 2011;Nordell, 2003;Yuqin et al, 2010). Therefore, industrial flaring and its effect on the environment, ecosystem and society have gained the attention of researchers, environmentalists and policy makers.…”
Section: Introductionmentioning
confidence: 99%